The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1007/bf02484390
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the conditions of fabrication and structure of cotton cellulose for viscose formation

Abstract: The effect of different regimes for each stage of fabrication of cotton cellulose on its supermolecular structure was evaluated by electron microscopic methods. It was shown that rigorous conditions of fabrication of cotton cellulose cause destruction and loosening of the surface and inner layers of the fibre. This indicates an increase in the reactivity of the cellulose and is promising for processing # into viscose fibres.As a function of the method of separation of cellulose, its structure has special featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies of production of cotton cellulose showed [25] that the basic characteristics which make it possible to process cellulose with the viscose method and spin viscose textile fibre with properties close to the indexes of the industrial product can be attained with the following process scheme: centricleaner washing, alkaline pulping, centricleaner washing, two-stage bleaching with sodium hypochlorite solution, acid wash, washing.…”
mentioning
confidence: 99%
“…Studies of production of cotton cellulose showed [25] that the basic characteristics which make it possible to process cellulose with the viscose method and spin viscose textile fibre with properties close to the indexes of the industrial product can be attained with the following process scheme: centricleaner washing, alkaline pulping, centricleaner washing, two-stage bleaching with sodium hypochlorite solution, acid wash, washing.…”
mentioning
confidence: 99%